Self-esteem and father presence : a study of young women at a South African university - Vilanculos, Esmeralda (My University, 2018)
Background: The development of self-esteem begins early on at childhood, and this is based on emotional and social growth. Earlier research studies demonstrate that children who co-reside with their biological fathers present with higher self-esteem. The impact of father presence on daughters in early childhood stages of life continues to shape their self-esteem in young-adulthood or adulthood stages. However, absent is research that studies how self-esteem relates to father presence and involvement in young women’s lives, particularly in the Global South. Moreover, there is a conspicuous absence of South African literature that addresses this association in samples of adolescents and young women. To address this limitation, the study aimed to investigate the association between daughters’ self-esteem and the three domains of father presence. The study also examined whether self-esteem differed based on the reasons for-father-absence or other selected socio-demographic variables. Specifically, the study intended to analyse the following hypothesis: 1. Daughters’ self-esteem will be positively related to the RF-Domain 2. Daughters’ self-esteem will be positively related to the BAF-Domain. 3. Daughters’ self-esteem will be positively related to the IFI-Domain. 4. Daughters’ self-esteem scores would not significantly differ based on the relationship status (Rel-Status), ethnicity, overall degree of closeness with the father (DCD), mothers’ educational level (Mother-Edu), co-residence status of the father (FC-Status), co-residence status of the father-figure (FFC-Status), degree of contact with the father if parents divorced/separated (DegC) or daughter’s age at father's death/permanent departure if father departed before the age of 18 years (AgeD) 5. Daughters’ self-esteem scores would not significantly differ based on the Reasons-for father-absence. Self-esteem and father presence: A study of young women at a South African university 6. AgeD, Rel-Status, Ethnicity, DCD, DegC, Mother-Edu, FC-Status, FFC-Status and relationship with the father domain (RF-Domain) have a significant contribution to the prediction of daughters’ self-esteem. Methods: A quantitative non-experimental correlational cross-sectional study was conducted with a purposive convenient sample of 250 undergraduate and postgraduate psychology female students aged between 18 and 24 years, registered with the University of the Witwatersrand. A self-reported online questionnaire was used to collect data during the month of November and December 2016. The IBM SPSS Statistics (version 24) was used for data analysis. Cronbach alpha analyses were used to calculate the internal reliabilities of the FPQ and self-esteem measures. A series of Pearson or Spearman’s correlations were used to establish the association between self-esteem and three domains of father presence. A series of one-way ANOVAs or independent samples t-tests were conducted to investigate whether there were significant differences in young women’s self-esteem based on ethnicity, degree of closeness, or other selected socio-demographic variables. A series of multiple linear regression analyses were conducted to predict self-esteem by ethnicity and DCD in conjunction with the subscales of the relationship with father domain of the father presence measure. Results: Self-esteem demonstrated a significant positive relationship with the RF domain of father presence (p < 0.05). Young women’s self-esteem demonstrated a partial significant relationship with the beliefs about the father or intergenerational family influences domains of father presence. Young women’s self-esteem differed based on the ethnicity or the reasons-for-father-absence (p < 0.05). However, a selected number of socio-demographic factors (i.e. AgeD, FFC-Status, FC-Status, Relationship-Status, or DegC) exhibited no significant differences in young women’s self-esteem (p > 0.05). Moreover, ethnicity in combination with the perceptions of the father’s influence, feelings about the father, mother’s support for the relationship with the father, physical relationship with the father or the father Self-esteem and father presence: A study of young women at a South African university mother relationship were significant predictors of self-esteem (p < 0.05), with ethnicity being the better predictor variable. However, DCD demonstrated no significant contribution in the prediction of self-esteem in any of the regression models. Discussion: The relationship between self-esteem and the three domains, namely the relations with the father, beliefs about the father, and the intergenerational family influences were partially consistent with previous research. Moreover, consistent with previous research, there were significant mean differences in self-esteem based on young women’s ethnicity, degree of closeness with father, and the mother’s educational level. Conclusions: the domains of father presence were associated or partially associated with young women’s self-esteem. Ethnicity predicted self-esteem in conjunction with each of the subscales of the father relationship domain. Recommendations: These findings suggest that researchers and clinicians should consider the role of ethnicity in combination with each of components of the relationship with the father domain of father presence as significant factors which predict daughters’ self-esteem. Researchers should also consider self-esteem to be associated with factors such as the respondents’ ethnicity, overall degree of closeness with the father, perceptions of the father’s influence, feelings about the father, mother’s support for the relationship with the father, physical relationship with the father, father-mother relationship, conceptions of God as the Father, negative sentiments of the mother’s relationship with her father, or the positive sentiments of the mother’s relationship with her father. Key words: adolescents, daughters, father absence, father involvement, father presence, self-esteem, South Africa, young women.
Submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report in the field of Community-Based Counselling Psychology In the Faculty of Humanities At the University Of The Witwatersrand, May 2018
Keywords: Self-esteem in adolescence--South Africa; Parent and child--South Africa; Absentee fathers--South Africa; Fathers and daughters--South Africa--Psychological aspects